Pengembangan Media Pembelajaran Berbasis Android Untuk Memfasilitasi Kebutuhan Pembelajaran Multiple Representation - Nur Candra Eka Setiawan; Oktavia Sulistina; Habiddin Habiddin; Rucira Pavita (Hydrogen: Jurnal Kependidikan Kimia, 2021)
During the Covid-19 pandemic, learning is done online. Many students experience difficulties and decreased learning achievement while carrying out online learning. The reaction rate practicum learning media used at the high school level does not yet represent macroscopic, submicroscopic, and symbolic chemical concepts and has not been adapted to online learning. Multiple chemical representations can be applied using android-based learning media so that students are expected to understand the concepts in the reaction rate practicum. Android-based learning media is used to support the learning process. The purpose of developing android-based learning media on the reaction rate practicum concept is to produce android-based learning media and determine its feasibility. The development model used is the 4-D model by Thiagarajan, et al. The product developed in the form of an android-based reaction rate practicum learning media for students at senior high school. Based on the validation results indicate that the module is very feasible to use by meeting the percentage of 88.8%. The results of the readability test on the module obtained a percentage of 84.5%, so based on this assessment the module is very suitable for students to use as a learning resource and learning process in the classroom.